Interactions exploring the functions of the human body - Lancraft, Thomas; Frierson, Frances ([S.l.] : John Wiley & Sons, 2005)
Series of programs focusing on the examination of physiological processes within each system of the body, using animations, interactivity, and clinical correlations to enhance students' understanding.
Foundations -- Regulation: the nervous and endocrine systems -- Support and movement: the skeletal and muscular systems -- Distribution: the cardiovascular and lymphatic systems -- Disease resistance: the integumentary, lymphatic, and immune systems -- Energy acquisition and use: the digestive system and metabolism -- Gas exchange and pH balance: the respiratory system -- Balancing fluids and pH: the urinary system -- Continuity: the reproductive systems and development.
Title from disc label; additional information from package.
System requirements (Windows): Pentium 166 or higher; 32 MB RAM; DVD-ROM drive; 800x600 screen resolution, hi color mode; Windows 98/Windows ME/Windows 2000/Windows NT, Windows XP; Windows sound card; Internet Explorer v5.0 or higher or Netscape Navigator v4.7.x/7.1; Pop-up blocker must be disabled.
System requirements (Macintosh): PowerPC G4 450 MHz; 256 MB RAM; 4x speed DVD-ROM drive; 800x600 resolution 256 colors; Mac OS X, v. 10.2 and above; Safari 1.0 and above, Netscape 7.0 and above, or Internet Explorer 5.2 and above; Pop-up blocker must be disabled.
Keywords: Physiology -- DVD